(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with acute calculous cholangitis at Nguyen Tri Phuong Hospital Methods: A descriptive case-series study was conducted, retrospectively reviewing the medical records of 133 patients with acute calculous cholangitis admitted and treated at the General Surgery Department from January 2023 to February 2025. Data were analyzed using Stata, presented as frequencies, percentages, medians, and interquartile ranges. Results: The median age of the study group was 66 (53–77) years; females accounted for 63.9%. Common comorbidities included hypertension (44.4%) and diabetes mellitus (29.3%). Abdominal pain (96.2%), fever (60.9%), and jaundice (36.8%) were the main symptoms. The median WBC was 13.8 G/L, CRP was 36.7 mg/L, and total bilirubin was 43.2 µmol/L. On ultrasound, intrahepatic bile duct stones were present in 75.9%. Among positive cultures, E. coli was the most common bacterium (40.3%). Conclusion: Patients with acute calculous cholangitis were mainly elderly females with comorbidities, presenting with typical clinical and paraclinical features of infection and biliary obstruction.